Avaliação de diferentes métodos de dispersão de microcelulose cristalina em pastas cimentícias - Fillus, Gisella (2023)
The present research assessed diverse methods for dispersing crystalline microcellulose (MCC) in an aqueous medium, aiming to formulate cementitious pastes. In accordance with the extant literature, the enhancement of properties in cement-based materials incorporating MCC is not universally guaranteed, owing to the challenges associated with its dispersion and proclivity for agglomeration. Consequently, this study conducted an analysis of aqueous suspensions prepared through two dispersive methods, namely ultrasonic bath and magnetic stirring, each applied for a duration of 5 minutes. Furthermore, two concentrations of MCC (0.6% and 0.8% relative to the mass of cement) were examined. Subsequently, the specimens underwent testing in both the fresh and hardened states at 14 and 28 days of hydration. Rotational rheometry tests revealed a reduction in the fluidity of cement pastes following the incorporation of crystalline microcellulose. Through flexural and compressive strength assessments, it was possible to deduce that the optimal concentration of crystalline microcellulose is contingent upon the dispersion method employed. Particularly noteworthy is the observation that magnetic stirring at a concentration of 0.8% did not yield improvements in mechanical properties, in contrast to ultrasonic agitation at the 28-day mark. Visual analysis of pores in the samples suggests that the introduction of crystalline microcellulose significantly increases pore quantity. However, samples subjected to the ultrasonic agitation method exhibited a reduction in larger pores and an augmentation in smaller pores, indicating efficient dispersion facilitated by the reduction of agglomerates.